Key Success Factors of Risk Management in the Procurement Process to Support the Domestic Product Utilization Enhancement Program - Oktaviyani, Tri; Saksono, Rochmad Nur Afsdy; Rahayu , Neneng Sri (Dinasti Publisher, 2025)
The domestic product usage policy can be strategically implemented through government procurement activities. In order to guarantee that every step of the procurement process is transparent, accountable, and in accordance with the direction of the domestic product usage policy, risk management is an essential component. The objective of this research is to determine and rank various key success factors (KSFs) for risk management in the procurement process in government institutions. This research was conducted in two stages, namely: (1) literature review, to identify the suitable KSF in a government context, and (2) Analytic Hierarchy Process (AHP), to prioritize KSFs based on the highest weight value. This study found that the priorities of KSFs for risk management in the procurement process to support the domestic product utilization enhancement program are (1) management commitment, (2) risk-aware culture, (3) business process integration, (4) adequate resources, (5) effective communication, and (6) training.